Strategi Gereja Dalam Meningkatkan Partisipasi Pemuda Untuk Mengikuti Komunitas Pemuridan - Alvin Alvin; Joko Prihanto; Yanto Paulus Hermanto (Logia, 2025)
The participation of young people in discipleship communities has become a crucial challenge for today’s church, as many youths only attend Sunday services without deeper involvement. This study employs a qualitative literature review approach, drawing data from books, journals, online sources, and the Bible, to analyze strategies for increasing youth engagement in discipleship. The findings show that warm relational bridges such as connections areas are important entry points, but strong and healthy discipleship groups are essential for sustaining growth. Small groups of 8–12 members, supported by intentional mentoring and leadership regeneration, create a setting where youths can grow spiritually, experience meaningful fellowship, and be equipped for future service. The study concludes that building relational culture, acceptance, and consistent leadership development are key strategies for churches to form committed young disciples and ensure the continuity of faith across generations. Keywords:  Youth participation, Discipleship, Church strategy